Direct evidence for neutrino flavor transformation from neutral-current interactions in the Sudbury Neutrino Observatory - Ahmad, Q; Allen, R; Andersen, T; Anglin, J; Barton, J; Beier, E; Bercovitch, M; Bigu, J; Biller, S; Black, R; Blevis, I; Boardman, R; et al. (2002)
The direct evidence for neutrino flavor transformation from neutral-current (NC) interactions in the Sudbury Neutrino Observatory was presented. The νe component of the 8B solar flux was calculated by using the NC, elastic scattering and charged current reactions. Results presented the first direct measurement of the total flux of active 8B neutrinos arriving from the sun and provided strong evidence for neutrino flavor transformation.